Case Study Evaluation of Road Network Connectivity in Center Banjarmasin: Studi Kasus Evaluasi Konektivitas Jaringan Jalan di Banjarmasin Tengah - Miftahul Ridhoni; Andi Achmad Priyadharma; Muhammad Yusuf Ridhani; Kiky Permana Setiawan (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
Road network configuration is a permanent element of urban morphology that influences spatial utilization patterns, mobility, and public accessibility. Good network connectivity encourages the use of active and public transportation, while low connectivity increases reliance on private vehicles. This study aims to evaluate the performance of road network connectivity in Banjarmasin City, focusing on Banjarmasin Tengah District as the City Service Center (PPK), and comparing it with other districts. The study uses a quantitative approach with spatial data analysis for the 2021–2025 period using ArcMap software. Three indicators are used: the Road Density Index, the Beta Connectivity Index, and the Gamma Connectivity Index, with road segments as the unit of analysis according to the Indonesian Road Capacity Guidelines. The results show that Banjarmasin Tengah District has the highest road density, reflecting the availability of relatively good physical infrastructure. The highest beta connectivity values ​​are also found in Banjarmasin Tengah and Banjarmasin Timur, although generally still in the low–moderate category. Meanwhile, gamma connectivity values ​​across all districts are relatively low, with an average of around 13% of optimal conditions. These findings indicate the need to improve connectivity between segments, particularly in local and neighborhood road networks, to support a more efficient and sustainable urban transportation system.